mTOR pathway: A potential therapeutic target for spinal cord injury - Yi Ding (Elsevier, 2022)
Spinal cord injury (SCI) is the most common disabling spinal injury, and the complex pathological process can eventually lead to severe neurological dysfunction. Many studies have reported that the mammalian target of rapamycin (mTOR) signaling pathway plays an important role in synaptogenesis, neuron growth, differentiation, and survival after central nervous system injury. It is also involved in various traumatic and central nervous system diseases, including traumatic brain injury, neonatal hypoxic-ischemic brain injury, Alzheimer's disease, Parkinson's disease, and cerebral apoplexy. mTOR has also been reported to play an important regulatory role in various pathophysiological processes following SCI. Activation of mTOR signals after SCI can regulate physiological and pathological processes, such as proliferation and differentiation of neural stem cells, regeneration of nerve axons, neuroinflammation, and glial scar formation, through various pathways. Inhibition of mTOR activity has been confirmed to promote repair in SCI. At present, many studies have reported that Chinese herbal medicine can inhibit the SCI-activated mTOR pathway to improve the microenvironment and promote nerve repair after SCI. Due to the role of the mTOR pathway in SCI, it may be a potential therapeutic target for SCI. This review is focused on the pathophysiological process of SCI, characteristics of the mTOR pathway, role of the mTOR pathway in SCI, role of inhibition of mTOR on SCI, and role and significance of inhibition of mTOR by related Chinese herbal medicine inhibitors in SCI. In addition, the review discusses the deficiencies and solutions to mTOR and SCI research shortcomings. This study hopes to provide reference for mTOR and SCI research and a theoretical basis for SCI biotherapy.